A Comparison of Different Slicing Planes in Preservation of Major Hippocampal Pathway Fibers in the Mouse - Xiong, Guoxiang; Metheny, Hannah; Johnson, Brian N.; Cohen, Akiva S. (Frontiers in Neuroanatomy, 2017)
The hippocampus plays a critical role in learning and memory and higher cognitive functions, and its dysfunction has been implicated in various neuropathological disorders. Electrophysiological recording undertaken in live brain slices is one of the most powerful tools for investigating hippocampal cellular and network activities. The plane for cutting the slices determines which afferent and/or efferent connections are best preserved, and there are three commonly used slices: hippocampal-entorhinal cortex (HEC), frontal, and transverse. All three slices have been widely used for studying the major afferent hippocampal pathways including the perforant path (PP), the mossy fibers (MFs) and the Schaffer collaterals (SCs). Surprisingly, there has never been a systematic investigation of the anatomical and functional consequences of slicing at a particular angle. In the present study, we focused on how well fiber pathways are preserved from the EC to the hippocampus, and within the hippocampus, in slices generated by sectioning at different angles. The postmortem neural tract tracer 1,1'-dioctadecyl-3,3,3'3'-tetramethylindocarbocyanine perchlorate (DiI) was used to label afferent fibers to hippocampal principal neurons in fixed slices or whole brains. Laser scanning confocal microscopy was adopted for imaging DiI-labeled axons and terminals. We demonstrated that PP fibers were well preserved in HEC slices, MFs in both HEC and transverse slices, and SCs in all three types of slices. Correspondingly, field excitatory postsynaptic potentials (fEPSPs) could be consistently evoked in HEC slices when stimulating PP fibers and recorded in stratum lacunosum-moleculare (sl-m) of area CA1, and when stimulating the dentate granule cell layer and recording in stratum lucidum of area CA3. The mossy fiber evoked fEPSPs could not be recorded in CA3 from frontal slices. In contrast to our DiI-tracing data demonstrating severely truncated PP fibers in frontal slices, fEPSPs could still be recorded in CA1 sl-m in this plane, suggesting that an additional afferent fiber pathway other than PP might be involved. The present study increases our understanding of which hippocampal pathways are best preserved in the three most common brain slice preparations, and will help investigators determine the appropriate slices to use for physiological studies depending on the subregion of interest.